2022
DOI: 10.1111/1462-2920.16122
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical variation in antimicrobial resistance in rivers is influenced by agriculture and is spread through bacteriophages

Abstract: Antibiotic resistance is currently an extensive medical challenge worldwide, with global numbers increasing steadily. Recent data have highlighted wastewater treatment plants as a reservoir of resistance genes. The impact of these findings for human health can best be summarized using a One Health concept. However, the molecular mechanisms impacting resistance spread have not been carefully evaluated. Bacterial viruses, that is bacteriophages, have recently been shown to be important mediators of bacterial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…With the antibiotics only being present in the oral cavity for a short time span, a significant upregulation of phages may not necessarily be expected, however, a significant change in the virome itself could be detected ( Abeles et al, 2015 ), indicating that a larger study may be able to identify such induction. Having demonstrated that stressors in environmental water can affect prevalence of resistance genes and carriage by bacteriophages ( Andersson et al, 2022 ), we thus set out to investigate if phage induction would take place in patients receiving oral antibiotics, and how this would affect the resistance profile.…”
Section: Discussionmentioning
confidence: 99%
“…With the antibiotics only being present in the oral cavity for a short time span, a significant upregulation of phages may not necessarily be expected, however, a significant change in the virome itself could be detected ( Abeles et al, 2015 ), indicating that a larger study may be able to identify such induction. Having demonstrated that stressors in environmental water can affect prevalence of resistance genes and carriage by bacteriophages ( Andersson et al, 2022 ), we thus set out to investigate if phage induction would take place in patients receiving oral antibiotics, and how this would affect the resistance profile.…”
Section: Discussionmentioning
confidence: 99%
“…One source of dispersal is phages, which carry ARGs and also mediate HGT (102). Exposure to contaminants, such as antibiotics, chemicals and heavy metals present in the environment, can lead to phage induction and new rounds of infection that result in ARG transfer (3). Interestingly, although at a much smaller scale, swarming bacteria, which migrate over surfaces using flagella, also disperse antibiotic-resistant microorganisms, in this case by transporting resistant antibioticdegrading bacteria to detoxify a new environment (48).…”
Section: Dispersal In the Environmentmentioning
confidence: 99%